Reliability Analysis for Standby System with Renewable, Repair and Preventive Maintenance - Alhajeri, Hana’a (Opción, 1970)
In present-day technology, a high level of reliability of systems is required. Recently, many authors have computed under different sets of assumptions and in varying degrees of generality the reliability function and the mean lifetime, for the renewable systems. The reliability of a renewable system, composed of n main units and one stand by, under a preventive maintenance activity. The reliability function and the mean lifetime are obtained for the cases of loaded, nonleaded (cold standby) and lightly loaded (warm standby) systems with repair and preventive maintenance. The results obtained before in [1, 4], in case of repair only, are derived from the present results as special cases.